(untitled) (The Research of Medical Science Review, 2025)
Background: Thyroid nodules are commonly detected, but histopathology, the gold standard for malignancy diagnosis, is invasive and costly. The 2014 British Thyroid Association ultrasound scoring system offers a non-invasive alternative, though it’s diagnostic accuracy remains controversial, prompting this study to assess its reliability. Objective: To assess diagnostic accuracy of British thyroid association 2014 classification ultrasound scoring in predicting malignant thyroid nodules taking histopathology as gold standard. Duration: Six months w.e.f 21-12-2023 to 20-06-2024. Methodology: After ethical approval, 145 patients who met the inclusion criteria were enrolled from the OPD and referred to the radiology department. Informed consent was obtained. Demographics such as age, BMI, neck circumference, smoking history, diabetes, hypertension, residence, and occupation were recorded. Patients underwent ultrasonography and were classified based on the British Thyroid Association 2014 guidelines. Biopsy samples were sent for cytology. Findings were documented, and data was analyzed using SPSS version 22.0. Results: The study included 145 participants, with a mean age of 45.5 years, 60% aged 20-50 years, and 66.2% female, with 63.4% classified as overweight/obese. Health conditions like hypertension (56.6%) and diabetes (43.4%) were common. Ultrasound scoring identified 40.7% as malignant, while histopathology confirmed 42.1%. The diagnostic performance of ultrasound scoring showed a sensitivity of 90.16%, a positive predictive value (PPV) of 93.23%, a negative predictive value (NPV) of 93.01%, and an accuracy of 93.10%. Stratification by subgroups showed no significant differences in malignancy prevalence. Conclusion: Ultrasound scoring proved to be a reliable method for predicting malignant thyroid nodules, offering high diagnostic performance. The study showed no significant differences in malignancy prevalence across subgroups. These results suggest that ultrasound scoring is a valuable non-invasive tool for thyroid nodule evaluation.